Contribution of Savings and Internal Lending Communities to the Youth Livelihood in Rwanda: The Case of Gikongoro Diocese Project 2006-2010 - Jacques, Sezikeye (Kabale University, 2023)
This study set out to assess the socio-economic impact of SILC on youth livelihood development through the increase in access to finances to boost business and income-generating activities within rural settings in Rwanda, as well as looking at possible challenges and limitations for a proper recommendation that may result in the expansion of several youth groups. The study's objectives were to assess the social economic impact of SILC on youth livelihood development in Gikongoro diocese, to determine whether SILC has increased youth access to financial services, and to determine the influence of SILC on youth starting small businesses.The study employed qualitative and quantitative methods of data collection, which included the use of questionnaires, the use of interview methods, observation, and also documentary methods while in the field. The findings were obtained, interpreted, discussed, and analyzed, and then later summarized in tables. The researcher went ahead to give a summary of the findings, conclusion, and recommendations of the report as they were given by the respondents. The findings clearly showed that savings and internal lending communities have a great impact on youth livelihood development in Gikongoro diocese in that they help in diversifying livelihood income strategies and financial assets. Also, they increase individual wealth and allow members to invest money in income-generating assets, though they face some problems in trying to enhance financial access to the youth, like corruption among the members of the groups, a lack of knowledge to handle finance issues among the youth since most of them are school dropouts, poor management accountability of funds given to many youth, and a failure to make proper decisions among many youth; but in a nutshell, they have contributed greatly towards improving the living standards of the youth in Gikongoro diocese.